2012
DOI: 10.1620/tjem.228.85
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies Are Associated with a Reduction of Interferon-β Efficacy during the Treatment of Japanese Multiple Sclerosis Patients

Abstract: Multiple sclerosis (MS) is a chronic immune-mediated inflammatory demyelinating disease of the central nervous system. Interferon-β (IFN-β) has been used as the first line therapy for MS treatment in Japan, but patients treated with IFN-β may develop antibodies, known as neutralizing antibodies (NAbs), which abrogate its therapeutic effects. Intramuscular IFN-β 1a and subcutaneous IFN-β 1b are currently available in Japan, but large-scale studies evaluating the prevalence and clinical implications of NAbs agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Real-world studies are in line with randomized clinical trials showing a negative impact of NAbs on clinical (Table 2) [10,[45][46][47][48][49][50][51][52][53]60] and MRI parameters (Table 4) [45,47,52]. Whereas all the observational studies showed an impact of NAbs on the RR or the time to first relapse, the negative effect of NAbs on progression of EDSS was evident in few studies and with low statistical significance ( Table 2).…”
Section: Clinical Relevance Of Nabssupporting
confidence: 60%
See 1 more Smart Citation
“…Real-world studies are in line with randomized clinical trials showing a negative impact of NAbs on clinical (Table 2) [10,[45][46][47][48][49][50][51][52][53]60] and MRI parameters (Table 4) [45,47,52]. Whereas all the observational studies showed an impact of NAbs on the RR or the time to first relapse, the negative effect of NAbs on progression of EDSS was evident in few studies and with low statistical significance ( Table 2).…”
Section: Clinical Relevance Of Nabssupporting
confidence: 60%
“…Consistent data came from clinical studies lasting more than 2 years, using all the three different IFNβ preparations, designed as placebo-control clinical trials [22,23,44], prospective real-world studies [10,[45][46][47][48][49][50][51][52] or propensity score studies [53].…”
Section: Clinical Relevance Of Nabsmentioning
confidence: 99%
“…The prevalence of NAbs in Japanese MS patients is similar to that in Caucasians, and NAb titres are also found to be associated with an increased disease activity in Asian populations 14. Cross-sectional studies of routine data performed in Sweden and Iceland reported a decrease in NAb seroprevalence from 32% in 2003–2004 to 19% during 2009–2010 15.…”
Section: Introductionmentioning
confidence: 72%
“…When patients showed breakthrough for interferon we also have a free support system measuring neutralizing antibody for IFNs at Tohoku Univesity. Because neurralizing antibodies are associated with a reduction of IFN beta efficacy during the treatment 15) .…”
Section: ) Ifnsmentioning
confidence: 99%